External Factors that Cause Dysmenorrhea in Adolescent Girls: Literature Review - Rizsya; Friska Realita; Noveri Aisyaroh (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Background: Puberty is important for physical and reproductive changes. Menstruation in adolescent girls is a focus, with dysmenorrhea (painful menstruation) a serious issue. WHO notes the high prevalence of dysmenorrhea in Indonesia, especially in adolescent girls. The government has responded through adolescent reproductive health programs and the regulated role of midwives. External factors such as stress, nutritional status, and fast-food consumption play an important role in dysmenorrhea in adolescents. Further understanding of these factors is necessary for a holistic solution. Objective: The aim of this study is to analyze research results related to external factors that cause dysmenorrhea in adolescent girls. Method: This research uses a literature review method by examining several related studies. Article sources come from ScienceDirect, PubMed, and Google Scholar, with keywords including risk factors for dysmenorrhea, stress levels, nutritional status, fast food consumption, and risk factors for dysmenorrhea. Results: From the search results, 8 national journals and 2 international journals were selected that were relevant to external factors causing dysmenorrhea in adolescent girls. All journals used were published in the last 5 years (2019–2021) and can be in Indonesian or English. Based on the results of a review of 3 international articles and 7 national articles, it was concluded that there are three external factors that contribute to the incidence of dysmenorrhea in adolescent girls, namely stress levels, nutritional status, and consumption of fast food. Conclusion: Based on a review of 10 articles, dysmenorrhea in adolescent girls is influenced by external factors such as stress levels, nutritional status, and consumption of fast food. Prevention can be done by maintaining a healthy diet, exercising regularly, and avoiding stressful situations.